Declarative Representation of Algorithms of Completion by Critical Pairs - Volkov, V. A. (Cybernetics and systems analysis, 2001)
A declarative representation of critical pairs for completion algorithms is described. The representation can be considered as a generic program that, after parametrization of some of its functions, realizes the Knuth-Bendix algorithm for solving the word problem in universal algebras or Buchberger algorithm for constructing Grobner bases of polynomial ideals. The properties of termination and correction are considered. A realization of the representation in the APS algebraic system is described. [PUBLICATION ABSTRACT]